Molecular prevalence and clinicopathological association of bartonella infection in cats presented to the University Veterinary Hospital, Universiti Putra Malaysia - Hassan, Ummukulthum Lawal (2015)
Feline bartonellosis is a bacterial infection caused by Bartonella species transmitted by the cat flea (Ctenocephalides felis). The disease is asymptomatic in a majority of cats but can be transmitted from infected cats to humans via inoculation or ingestion of flea excrement through scratches or bites. Human Bartonella infection has a variety of clinical manifestations such as bacillary angiomatosis, endocarditis, neuroretinitis and cat scratch fever. Cat owners and veterinarians who are in direct contact with cats are at risk of infection. However, despite the zoonotic potential of the disease, there is paucity of information on feline and human bartonellosis in Peninsular Malaysia. Hence, this study was conducted to determine the molecular prevalence of Bartonella and if the presence of this bacteria is associated with any clinicopathological findings in cats presented to the University Veterinary Hospital (UVH), University Putra Malaysia (UPM). Of 284 blood samples collected from healthy and ill cats with the median age of 2 years 10 months, presented to the UVH, 48 were PCR positive for the internal transcribed spacer region (ITS) in Bartonella species with an overall prevalence of 16.9% (n=48) (95% CI: 12.8-21.9). Univariate analysis of demographic data showed the detection rate to be significantly associated with younger cats, below 2 years of age [OR= 1.690 (95% CI: 0.989-2.889), p-value = 0.051]. Ocular discharge was the only clinical sign observed to be associated with the presence of Bartonella [OR= 3.211 (95% CI: 1.422-7.248), p-value= 0.003], while laboratory results revealed significant association of bartonellosis with neutrophilia [OR: 2.24 (95% CI: 1.131-4.452, p-value = 0.019] and monocytosis [OR: 2.476 (95% CI: 1.154-5.312), p-value = 0.017]. While thesefindings are statistically associated, a causal relationship cannot be implied as other concurrent diseases could not be ruled out. Other hematological findings such as anemia, reticulocytosis, lymphocytosis, eosinophilia and azotemia,were not significant. This study reveals a significant presence of Bartonella infection in pet cats with various medical conditions presented to the University Veterinary Hospital,'Faculty of Veterinary Medicine, UPM. In view of the potential public health risk of feline bartonellosis especially amongst children, the elderly and immunosuppressed individuals, there is the need to educate cat owners on the latent infection of Bartonella and its zoonotic risk and the importance of flea control in their pet cats.